INTEGRATED SYSTEM IN FORECASTING STOCKS OF GOODS USING THE EXPONENTIAL SMOOTHING METHOD - Ricky Martin; Johan Johan (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
Determining the stock of goods is mandatory for a company of buy and sell goods, especially when there are many types of goods to sell. One of the companies that means is PT. Capella Dinamik Nusantara. The company is one of the largest Honda motorcycle distributor companies in Riau. PT. Capella Dinamik Nusantara also sells and purchases Honda motorbike spare Parts for its customers. Considering that there are quite a lot of types of Honda motorbikes and for one Honda motorbike there are already a lot of spare Parts, a system is needed that is able to store all motorbike data and spare Parts, and if possible can help predict the stock of items needed. This research aims to create a decision support system that can help PT. Capella Dinamik Nusantara in predicting the amount of spare part stock needed. The method used in this system is the Exponential Smoothing method with the programming language used is the PHP language which makes this system a Web-based system that is used locally.